The Effect of Work Environment, Work Stress, and Compensation on Employee Performance at PT. Indomarco Adi Prima Magelang Branch - Lestari, Sandra Widya; Hikmah, Khoirul (Strata International Journal of Social Issues, 2025)
This study investigates the influence of work environment, work stress, and compensation on employee performance at PT. Indomarco Adi Prima Magelang Branch. The background of the research highlights performance issues reflected in suboptimal performance metrics and increased absenteeism, presumably due to unfavorable workplace conditions, heightened stress, and compensation-related concerns. A quantitative approach was employed, utilizing a questionnaire distributed to all 57 employees using saturated sampling. The data were analyzed through multiple linear regression using SPSS version 25. The findings reveal that work environment, work stress, and compensation have a simultaneous and significant positive effect on employee performance, as indicated by the F-test (significance value = 0.000). Individually, each variable also shows a significant positive influence, supported by t-test results with all significance levels below 0.05. These results underscore the importance of a supportive work environment, effective stress management, and timely compensation in enhancing employee performance. The study contributes theoretically by confirming prior models and practically by offering strategic insights for human resource development in the distribution sector. Future research is advised to explore additional variables such as leadership style and organizational culture and to consider a qualitative or mixed-methods approach for a more holistic understanding of performance determinants.